Approbation of the Method for Examining the Performance of Seafloor Observatory Sensors Using Distant Earthquakes Records - Nosov, Mikhail; Karpov, Viacheslav; Sementsov, Kirill; Kolesov, Sergey; Matsumoto, Hiroyuki; Kaneda, Yoshiyuki (Frontiers in Earth Science, 2021)
An algorithm is presented for testing the calibration accuracy of both z-accelerometers and pressure gauges (PG) installed in seafloor observatories. The test is based on the linear relationship between the vertical acceleration component of the seafloor movement and variations of the seafloor pressure, which is a direct consequence of Newton's 2-nd law and holds valid in the frequency range of ``forced oscillations''. The operability of the algorithm is demonstrated using signals registered by 28 observatories of the DONET-2 system during 4 earthquakes of magnitude M_w~8 that took place in 2018-2019 at distances from 6 up to 15.5 thousand km.